Pemodelan dan Evaluasi Proses Bisnis Berdasarkan Hasil Ekstraksi Event Log dengan Menerapkan Process Mining pada Divisi Produksi PT. Kutai Timber Indonesia Kota Probolinggo - Cahyaningtyas Sekar Wahyuni; Nanang Yudi Setiawan; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Kutai Timber Indonesia Kota Probolinggo is a manufacturing company focusing on a timber production and marketing in Indonesia. In such a large company, Standard Operational Procedure (SOP) is definetly used to support the business process. In fact, there is a certain deviation from what is expected to happen and what is actually happened. This deviation might lead to fraud. Because of this, evaluation should be done so that this deviation will not harm the company. In this case, the evaluation is done by extracting event log from the ERP using Disco Tools and ProM Tools and implementing Process Mining as a method. It was found that there are 46 cases do not match the SOP from total 68 cases received in a month. The evaluation results show that the SOP model has fitness 0.88 and structural appropriateness 1.0 because the generated model is derived from YAWL simulation, so the process flow fits to the expected business process. Meanwhile, the model which is generated from event log ERP system has fitness 0.81 and structural appropriateness 0.421 because the activity contained in ERP has many variations and inconsistencies such as repetitive activities, deleted activities, and inserted activities, so that the model can not fully described all traces in the event log.